Research on Indoor Health Lighting Design Based on Silicon Substrate Golden Light LED Technology - Zhuoyi Jiang; Yeqing Zhu; Yihan Wang; Yangyang Wei (Buildings)
Silicon substrate golden light LED, as an emerging blue-light-free health lighting technology, has become one of the key technologies for home health lighting environments. This study uses silicon substrate golden light LED as the lighting source for home lighting, and based on the lighting demands of two indoor types, employs DIALux Evo lighting simulation software to simulate the indoor lighting environment. First, the simulated lighting data for various indoor areas are compared with the national lighting standards (GB/T50034-2024) to verify whether the lighting type meets the home lighting requirements. Next, a comparison is made between the lighting efficiency of silicon substrate golden light LED and a reference sample LED to validate whether the silicon substrate golden light LED possesses high lighting efficiency and low power consumption. Finally, long-term exposure to both the silicon substrate golden light LED and reference sample LED is used to record the secretion levels of melatonin in the human body. The experimental results show that the silicon substrate golden light LED not only provides sufficient home lighting but also demonstrates high efficiency and low power consumption. Additionally, under the illumination of silicon substrate golden light LED, the melatonin secretion concentration significantly increases to (960 ± 15) pg/mL after 2.5 h of exposure, which is 8.2 times higher than that of the conventional LED group (t = 12.34, df = 14, p < 0.001). The silicon substrate golden light LED technology provides a feasible solution for home health lighting design by creating a zero-blue-light health lighting environment.